A rotation angle sensor using the magnetooptic modulator on a bimorphic element - Linchevskyi, I.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
A rotation angle sensor based on the magnetooptic modulator on a bimorphic element under the magnetomechanical resonance is presented. It is shown that, due to the spatial distribution of the angle of rotation of the polarization plane over the cross section of a light beam, the threshold sensitivity in determining the angular parameter is 2.6 · 10−5 rad if the polarimeter works at the maximum of the first harmonic of the signal.